FORMUASI PERONA PIPI DENGAN KOMBINASI PEWARNA EKSTRAK BUAH BUNI (Antidesma bunius L) DAN EKSTRAK KELOPAK ROSELLA (Hibiscus sabdariffa L) SEBAGAI PEWARNA - Marliana, Elsa; Taurhesia , Shelly; Setyahadi , Siswa; Azzahra , Fauzia (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
The coloring agent plays important role in blush on preparation. Antidesma bunius L fruit and Hibiscus sabdariffa L flower are natural and harmless colorants. Both have anthocyanin content, which contributes to their color. In this study, the formulation of blush using a combination of Antidesma bunius fruit extract and Hibiscus sabdariffa L flower is developed. pH, temperature, and light intensity can all have an impact on anthocyanin stability. The extraction process is carried out using the maceration method, with 70% ethanol as the solvent and citric acid added to maintain the stability of the anthocyanin. Blush on is developed as a cream with a combination of both extracts in varying concentrations. The combination of both extracts not only maintains the pigment's stability at pH 3, 4, and 5, but also increases antioxidant activity, as a highly potent antioxidant with an IC50 value of 40 ppm. The blush on formulation using a 2:1 ratio of Antidesma bunius L fruit extract and Hibiscus sabdariffa L flower extract, with concentration of 80 times IC50 (F3K), shows sufficient physical qualities, antioxidant activity (IC50 = 231.55 ppm), and stable pigments. Based on these findings, the combination of Antidesma bunius L fruit extract and Hibiscus sabdariffa L flower extract could be used as an alternative natural coloring in cosmetics with antioxidant activity.